Comparison of Soil Higher Fungal Communities between Dead and Living Abies koreana in Mt. Halla, the Republic of Korea. Issue 5 (2nd September 2020) - Kim, Chang Sun; Jo, Jong Won; Lee, Hyen; Kwag, Young-Nam; Cho, Sung Eun; Oh, Seung Hwan
Abstract: To improve our understanding of the relationship between soil higher fungi (belonging to Ascomycota and Basidiomycota) and Abies koreana, we surveyed A. koreana soil fungal communities in a forest in Mt. Halla, Jeju Island, Korea by next-generation sequencing (Illumina Miseq). To confirm the soil higher fungal communities, we collected two types of soils from a defined plot: soils with dead (AKDTs) and living A. koreana (AKLTs), respectively. Soil fungi were classified into 2 phyla, 19 classes, 64 orders, 133 families, 195 genera, and 229 OTUs (895, 705 sequence reads). Nonmetric multidimensional scaling (NMDS) showed significantly different soil higher fungal communities between AKDTs and AKLTs ( p < .05). In addition, the saprophyte composition was significantly affected by A. koreana status ( p < .05). The proportion of the mycorrhizal Clavulina spp. was different between soils with AKDTs and AKLTs, suggesting that Clavulina spp. may be a crucial soil fungal species influencing A. koreana . This study will lead to a better understanding of the ecological status of A. koreana in Mt. Halla. In addition, this study could be useful for the conservation and management of A. koreana habitats.